2022
DOI: 10.1002/aur.2782
|View full text |Cite
|
Sign up to set email alerts
|

Autistic people outperform neurotypicals in a cartoon version of the Reading the Mind in the Eyes

Abstract: Prior research suggests that while autistic people may demonstrate poorer facial emotion recognition when stimuli are human, these differences lessen when stimuli are anthropomorphic. To investigate this further, this work explores emotion recognition in autistic and neurotypical adults (n = 196). Groups were compared on a standard and a cartoon version of the Reading the Mind in the Eyes test. Results indicated that autistic individuals were not significantly different from neurotypicals on the standard versi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…On the other hand, ASD individuals spent a shorter time looking at the robot face and showed increased positional variability, indicating that ASD individuals use visual sensing mechanisms differently than TD individuals when gathering information from a simulated social face. This particular finding may contribute to the body of evidence that ASD individuals process cartoon-like faces better than human faces (Cross et al, 2022;Rosset et al, 2010).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…On the other hand, ASD individuals spent a shorter time looking at the robot face and showed increased positional variability, indicating that ASD individuals use visual sensing mechanisms differently than TD individuals when gathering information from a simulated social face. This particular finding may contribute to the body of evidence that ASD individuals process cartoon-like faces better than human faces (Cross et al, 2022;Rosset et al, 2010).…”
Section: Discussionmentioning
confidence: 57%
“…Yet autistic individuals show both qualitative and quantitative differences in the processing of faces (Tang et al, 2015). Researchers have shown that autistic individuals may process cartoon faces easier than human faces (Cross et al, 2022;Rosset et al, 2010) as they may contain fewer dynamic facial expressions and eye movements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several reasons why autistic people may develop a specific interest in cartoon animation that is significantly elevated compared with neurotypicals, as research suggests (Anthony et al, 2013). The exaggeration inherent to anime (Liu et al, 2019) may make the emotional expression of characters particularly salient (Rozema, 2015), which autistic people may find helpful when decoding emotions (Atherton & Cross, 2021; Brosnan et al, 2015; Cross et al, 2022). For instance, anime faces have simplified shapes and a paucity of complex textures, which allow them to emphasize only the most salient aspects relevant to face identification with exaggerated expressions that powerfully convey meaning (Lu, 2009).…”
Section: Dsm-5 Criteriamentioning
confidence: 99%
“…Appreciation for anthropomorphism is also found in autistic populations. For instance, autistic people in the U.K. report elevated rates of personification (White & Remington, 2019), and autistic participants from the United Kingdom and the United States show an interest and aptitude for seeing the human in the non-human (Atherton & Cross, 2018, 2019, 2021; Atherton et al, 2018, 2022; Cross et al, 2019, 2022). A considerable body of research from Western and non-Western countries links anthropomorphism to autism (see Atherton & Cross, 2018, for a review).…”
Section: Dsm-5 Criteriamentioning
confidence: 99%